Immunohistochemical Study of Laminin-332 γ2 Chain and MMP-9 in High Risk of Malignant Transformation Oral Lesions and OSCC - Eline Manhães Reid Silva; Vanessa Morais Freitas; Willian Grassi Bautz; Liliana Aparecida Pimenta de Barros; Letícia Nogueira da Gama de Souza (eJournal of Oral Maxillofacial Research)
Objectives: Oral squamous cell carcinoma is associated with alterations in basement membrane. Laminin-332 is present in basal lamina and performs multiple biologic effects by γ2 chain. Matrix metalloproteinase acts disrupting extracellular components and was related to poor prognosis in cancer. Here, molecular profile of laminin-332 γ2 chain and matrix metalloproteinase-9 was assessed in oral lesions.